ANALISIS EFEKTIVITAS KAMPANYE PEMASARAN STORYTELLING PADA PLATFORM AZARINE COSMETIC UNTUK MENINGKATKAN BRAND IMAGE DAN BRAND TRUST SEBAGAI MEDIASI TERHADAP NIAT PEMBELIAN KONSUMEN - Ruruh Ayu Utami; Kussudyarsana Kussudyarsana (ITB AAS INDONESIA, 2024)
This research combines concepts related to marketing, communication, and consumer psychology to test hypotheses about the effectiveness of storytelling marketing campaigns on social media platforms focused on the Azarine brand, which is a local brand in Indonesia with a variety of products that have been recognized by the public. The research design used in this study is included in the type of quantitative research. This research uses the Partial Least Square (PLS) method. The results of the effectiveness of the storytelling marketing campaign on the Azarine cosmetics platform to improve brand image and brand trust as mediation on consumer purchase intentions, it is found the storytelling marketing campaign has a positive and significant effect on consumer purchase intentions, the first hypothesis is supported, the storytelling marketing campaign has a positive and significant effect on brand image, so the second hypothesis is supported, the storytelling marketing campaign has a positive and significant effect on brand trust, so the third hypothesis is supported, Brand trust has no positive and significant effect on consumer purchase intentions, so the fourth hypothesis is rejected and the last brand image has a positive and significant effect on consumer purchase intentions, so the fifth hypothesis is supported. Keywords : Marketing, Storytelling, Brand Image, Brand Image, Consumer